Discharge-drawdown relationship of eccentric wells - Birpinar, ME; Gazioglu, SA (ASCE-AMER SOC CIVIL ENGINEERS, 2002)
In the literature approximate and exact theoretical equations are presented for steady-state flow toward a discharging well, which is located eccentrically in a circular aquifer along whose outer cylindrical boundary either the drawdown or the flux is zero. This paper presents the results of using a physical model to test the validity of an analytical solution that describes drawdown for a well, which is placed eccentrically in a circular island aquifer. It is constructed in a sandbox model with several wells to conduct numerous steady-state tests. This study shows that the analytical equations are valid for small drawdowns. However, the equations do not represent higher drawdowns in the wells that are eccentrically located in the circular island model under steady-state flow in an unconfined aquifer.
Keywords: drawdown; wells; aquifer; steady flow; Engineering; Environmental Sciences & Ecology; Water Resources